Contemporary Liquid Brine Exploration on Mars: From Spectral Unmixing to Subpixel Mapping. Issue 3 (20th March 2019) - Zhong, Y.; He, D.; Luo, B.; Zhang, L.
Abstract: Water is a critical symbol for the existence of life in deep space exploration, and thus, the confirmation of the existence of liquid water on the contemporary Martian surface is important for the future studies of the hydrologic cycle and potential life on Mars. The main Mars observation system at a global scale is the Mars Reconnaissance Orbiter; however, this system has several drawbacks, that is, it cannot simultaneously resolve the features narrower than a few meters and scrutinize the surface composition both physically and chemically, leading to deficient and unsophisticated aqueous activity detection. Therefore, in this study, a joint endmember extraction, spectral analysis, and subpixel mapping technique, which we refer to as a joint processing pipeline, was applied to accommodate the detailed spatial information with the composition information in the physical and chemical aspects through luxuriant spectra. The validation of the proposed joint processing pipeline is described in the experimental part, with a case study of the megadune in the Russell Crater of Mars. The experimental results not only confirm the superior performance of the proposed pipeline in the accurate mapping and retrieval of Mars surface geology but also provide spectral evidence for the confirmation that hydrated material existed in the Russell Crater. Plain Language Summary: Water is essential for life, and thus the search for life on Mars can be achieved by searching for water‐related material on the Martian surface, which is exactly what we have aimed at in this paper. Over the past decades, many geophysical phenomena have been increasingly observed to have a close relationship to the flow of contemporary liquid water. In this paper, the Martian surface water was detected and recognized through the remotely sensed images obtained from the Mars satellites, which together provide a global view of the Martian surface and luxuriant spectral information for uniquely and diagnostically recognizing water‐related material. A Martian surface thematic map concerning water‐related material was also generated, describing the geospatial distribution of the water component, for the future hydrologic research and the study of potential life on Mars. Key Points: Contemporary liquid brine exploration based on hyperspectral image processing Joint endmember extraction‐spectral unmixing‐subpixel mapping processing pipeline for Mars hyperspectal image processing The detection and recognition of Recurring slope lineare (RSL), which was speculated to be reserved water